Syukur dalam Perspektif Al-Qur’an: Studi komparasi tafsir ibn katsir dan Tafsir Al Ibriz - Komaru Zaman; Lilis Amaliya Bahari (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2023)
This research is a type of qualitative research which is library (Library Research) by using descriptive analysis. As for the results of this research, the author concludes that gratitude in the Al-Qur'an, interpreted by Ibn Kathir and Al-Ibriz, is to be thankful, acknowledge blessings and show them by praising. Or more fully, gratitude is the visible influence of Allah Ta'ala's favor on the words of His servants in the form of praise, on the heart in the form of recognition, and on the limbs in the dimension of obedience or compliance. The point is to repay Allah Ta'ala's favors by means of words, deeds, and accompanied by the intention to always remember Him. Comparison of two interpretations in interpreting the word gratitude, namely: Firstly, according to Tafsir Ibnu Katsir, gratitude is acknowledging the blessings that Allah has given by mentioning them verbally. And use these pleasures to obey Allah Ta'ala so that Allah increases these pleasures and stays away from disbelief in order to avoid His punishment. Second, according to Tafsir Al-Ibriz, gratitude is acknowledging the blessings that Allah has given by mentioning them verbally. A servant's devotion to Allah Ta'ala will not increase his kingdom/power as creator, but a servant's gratitude and devotion will actually increase the servant's own blessings.